Comparative Analysis of the Operation of Social Media Channels by 156 Foreign Embassies in Japan: Focusing on the use of Twitter and Facebook Accounts in Communication with Japan - NISHIKAWA, Junko (Journal of Socio-Informatics, 2022)
Governments and embassies in various countries have opened social networking accounts and are engaged in online communication activities. Social media usage plays a significant role in diplomacy today. However, research on online communication by foreign countries with Japanese society is not sufficient to advance the substantive discussion.This paper aims to understand the actual situation of online diplomatic communication with Japanese society conducted by 156 countries that have embassies in Japan through a comparative analysis of their operations of social media channels. First, this study investigated whether the 156 embassies have opened accounts on the two platforms, Facebook and Twitter. The study identified 89 Twitter accounts and 99 Facebook pages of 119 embassies based in Tokyo, and reviewed the openings of these accounts starting from the early days of social media. Then, a detailed analysis of the Twitter accounts was conducted—the accounts were mapped according to the correlation between the average monthly growth of followers, the average monthly number of tweets, and the degree to which Japanese language was used in the tweets of each account.The results revealed that more than three-quarters of the 156 countries are on social networking sites. In contrast, only a limited number of countries use social media as a public diplomacy tool to communicate with the Japanese public. In addition to major Western countries, medium and small countries tweeting in Japanese are also considered relatively strategic in operating their accounts.